Effect of radiation on blood volume in low-grade astrocytomas and normal brain tissue: quantification with dynamic susceptibility contrast MR imaging. - Wenz, Frederik; Rempp, Katrin; Hess, Thomas; Debus, Jürgen; Brix, Gunnar; Engenhart, Rita; Knopp, Michael V.; Kaick, Gerhard van; Wannenmacher, Michael (American journal of roentgenology, 1996)
The purpose of this study was to determine whether it is possible to measure radiation-induced changes in blood volume in low-grade astrocytomas and in normal brain tissue. - The passage of a bolus of gadopentetate dimeglumine was monitored on a series of 55 T2*-weighted simultaneous dual fast low-angle shot MR images with a standard 1.5-T MR imaging system. Absolute blood volumes were calculated as the area under the tissue concentration-time curve in regions of interest and normalized to the arterial input function. We performed 41 examinations on 19 patients with grade II astrocytomas. For comparison, 13 patients were studied after whole-brain irradiation. - A reduction in blood volume (mean +/- SD in milliliters per 100 g) within the tumors from 12.2 +/- 8.7 to 6.5 +/- 5.3 after fractionated conformation radiotherapy was detected, although there was no consistent pattern in different patients. An insignificant reduction was noted in normal gray (9.2 +/- 2.8 to 7.4 +/- 3.2) and white (4.4 +/- 1.9 to 4.1 +/- 2.3) matter outside the target volume. Conversely, we observed a significantly lower blood volume in gray (6.3 +/- 1.2) and white (3.1 +/- 1.0) matter after whole-brain radiotherapy. - Our results show that a reduction of blood volume in astrocytomas and normal brain tissue after radiotherapy can be quantified by use of dynamic susceptibility contrast MR imaging. Thus, functional monitoring of tumor response and of normal tissue effects becomes possible.